Learning from users for radical innovation - Christoph Lettl; Cornelius Herstatt; H-G. Gemuenden (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2004)
In today's environment of rapid technological change companies can not rely on incremental innovations alone. To sustain long-term competitiveness companies need to develop radical innovations as well. Such innovations typically incorporate new and highly complex technologies, create new markets or shift existing market structures, and require user learning as they often induce significant behaviour changes on side of the users. To systematically develop radical innovations firms need to involve the proper actors. One such important external actor in the development process of new products is the user. Our study focuses on the question what kind of users are able to actively contribute to the development of radical innovations and what firms can learn from them to improve their innovative capability. A multiple case study analysis was conducted in the field of medical technology. Five radical innovation projects were selected including medical robots and computer-assisted navigation systems. The case study analysis reveals that users with a unique set of characteristics can contribute substantially to the development of radical innovations. These users have a high motivation toward new solutions, are open to new technologies, possess diverse competencies, and are embedded into a very supportive context. Manufacturers that took over the ideas and prototypes of the inventive users benefited significantly. By learning from these users, firms were able to significantly improve their radical innovative capability. The paper contributes to technology and innovation management research in two ways. First, by exploring critical user characteristics for distinct phases of the radical innovation process, we provide first insights how manufacturing firms can more effectively identify and leverage valuable users for their radical innovation work. Thereby, we highlight the involvement of capable users as an effective learning mechanism to improve the radical innovation capability of a firm. Second, new perspectives on lead user research are provided by enriching the lead user concept with other crucial characteristics of innovative users.
urn:nbn:de:gbv:830-opus-1292
Keywords: 650; Produktinnovation; Produktentwicklung; Benutzer / Beteiligung